grounding em aulas de educação física escolar: uma análise pela bioenergética - Rocha, Diane Ferraz Lopes da (2014)
The aim of this study was to analyze the postural grounding, conceived as the psycho-corporal experience contact with the own body, the ground and reality, in activities during physical education classes with male and female students aged between 10 and 13 years, establishing a connection between such activities and the bioenergetics‟ principles. According to the theoretical model of Bioenergetics' Analysis, the grounding corresponds to be self-sustaining process with balance and ability of self-expression, a process in which the individual develops contact with himself, with the space, with his internal and external reality, in the physical, symbolic and emotional levels. Such process promotes cohesion between the movement, the feeling and the expression and coherence between the psychological and corporal functioning. From this theoretical model, it was asked: In which activities of Physical Education the postural grounding is required? To collect data, a protocol of observation was developed specifically for the study, besides the semi-structured interview. Analyzing the results through the categorical content analysis of Bardin, it was concluded that therapeutic postures systematized in the Bioenergetics Analysis are experienced in Physical Education classes through activities that require erect posture, not rigid, equilibrated spine, knee joints slightly flexed, body weight on the rounded part of the feet, forward, centering on the abdomen and the ground movements that tend to move up and down with balance, to receive , release , trap, dribble, pass or kick a ball, or even to advance in space in games like basketball and soccer and in the activities of jump rope, wheelbarrow and catch the dragon‟s tail, for example, developing the grounding. In this process, to have a higher level of consciousness and more assertive response, teachers need intentional interventions in educational planning, which are suggested in this work.